Editorial for Localising the Sustainable Human Right to Water - Otto Spijkers (Utrecht University School of Law, 2020)
This Special Issue on Localising the Sustainable Human Right to Water begins with contributions focused on a global and more general perspective. These contributions provide a general introduction to the topic of the sustainable human right to water. It then shifts perspective to provide regional contributions, and finally zooms in to contributions focused on the implementation of this right at the national level.